2018
DOI: 10.3389/fnut.2018.00043
|View full text |Cite
|
Sign up to set email alerts
|

Minding One's Reach (To Eat): The Promise of Computer Mouse-Tracking to Study Self-Regulation of Eating

Abstract: In this review, we present the case for using computer mouse-tracking techniques to examine psychological processes that support (and hinder) self-regulation of eating. We first argue that computer mouse-tracking is suitable for studying the simultaneous engagement of—and dynamic interactions between—multiple perceptual and cognitive processes as they unfold and interact over a fine temporal scale (i.e., hundreds of milliseconds). Next, we review recent work that implemented mouse-tracking techniques by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…In order to capture the self‐regulation process as it unfolds, researchers can take advantage of tracing methods—including eye‐tracking and mouse‐tracking methodologies—to more directly observe how people make decisions in a given moment (e.g., Freeman, ; Freeman & Ambady, ). This is especially relevant to self‐regulation research, as such goal‐related decisions often occur automatically (i.e., in a few hundred milliseconds) and sometimes even unconsciously (see Lopez, Stillman, Heatherton, & Freeman, for a more detailed review). For example, research using mouse tracking to assess self‐control conflict found that people generally experience conflict when choosing between goal‐congruent (e.g., healthy food) and more tempting (e.g., unhealthy food) options (relative to a comparison group; e.g., food vs. non‐food item); however, those with higher levels of trait self‐control experienced less conflict (Stillman, Medvedev, & Ferguson, ).…”
Section: Finding the Middle Groundmentioning
confidence: 99%
“…In order to capture the self‐regulation process as it unfolds, researchers can take advantage of tracing methods—including eye‐tracking and mouse‐tracking methodologies—to more directly observe how people make decisions in a given moment (e.g., Freeman, ; Freeman & Ambady, ). This is especially relevant to self‐regulation research, as such goal‐related decisions often occur automatically (i.e., in a few hundred milliseconds) and sometimes even unconsciously (see Lopez, Stillman, Heatherton, & Freeman, for a more detailed review). For example, research using mouse tracking to assess self‐control conflict found that people generally experience conflict when choosing between goal‐congruent (e.g., healthy food) and more tempting (e.g., unhealthy food) options (relative to a comparison group; e.g., food vs. non‐food item); however, those with higher levels of trait self‐control experienced less conflict (Stillman, Medvedev, & Ferguson, ).…”
Section: Finding the Middle Groundmentioning
confidence: 99%
“…In order to capture the self-regulation process as it unfolds, researchers can take advantage of tracing methods -including eye-tracking and mouse-tracking methodologies -to more directly observe how people make decisions in a given moment (e.g., Freeman, 2018;Freeman & Ambady, 2010). This is especially relevant to self-regulation research, as such goalrelated decisions often occur automatically (i.e., in a few hundred milliseconds) and sometimes even unconsciously (see Lopez, Stillman, Heatherton, & Freeman, 2018 for a more detailed review). For example, research using mouse-tracking to assess self-control conflict found that people generally experience conflict when choosing between goal-congruent (e.g., healthy food) and more tempting (e.g., unhealthy food) options (relative to a comparison group; e.g., food vs.…”
Section: Finding the Middle Groundmentioning
confidence: 99%
“…Recent research in other decision-making domains has highlighted the usefulness of studying peoples' mouse trajectories in computer-based tasks. This research has focused on using the mouse trajectories to infer how strongly decision-makers favor their chosen options [30][31][32][33][34][35][36] . We reasoned that it should be possible to similarly use mouse trajectories to infer how strongly decisionmakers expect particular outcomes.…”
mentioning
confidence: 99%